Incorporating research-based teaching techniques in E-learning to teach English articles - Gillian, Edward; Lew, Robert (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article presents evidence about research-based teaching techniques that aided making the e-learning tool designed for this research more effective than traditional teaching methods when teaching English articles (e.g. ‘a’, ‘an’, and ‘the’). The techniques employed were: Master’s binary schema, explicit instruction, chunking, and direct feedback. Master’s binary schema (Master 1988, 2003) is an easy-to-grasp and detailed method of teaching English articles. Explicit instruction is the provision of clear and simple instruction of specific target structures (Troia & Graham 2002); in this study, the focus is on English articles. Chunking is the splitting of longer instructions into smaller segments for easier processing (Coufal 2002). Direct feedback for written texts is when responses are placed above, below, or near the inappropriate target structure to guide students towards appropriate use of structures (Bitchener & Knoch 2010). The main study results strongly indicated that the elearning tool was more effective than the traditional teaching techniques employed in this study. For the overall results by stage and group, the e-learning group achieved significantly better results than the control group. The main study results provide valuable quantitative evidence about the research based teaching techniques incorporated into the e-learning tool for English article usage teaching and for the effectiveness of e-learning in the English grammatical structure teaching.